Penggunaan Bahasa Prokem dalam Media Whatssup Grup Karang Taruna - Hanifatu Rissalatin; Suparmin Suparmin; Muhlis Fajar Wicaksono (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study was to describe the language of the youth program program in the whatsapp grub media. This research uses descriptive qualitative research method. The data collected is in the form of words, using reading, and sorting techniques. Data analysis techniques with distributional techniques that analyze the data as it is. The basis for determining distributional techniques is the technique of selecting data based on certain criteria from a grammatical perspective in accordance with the natural characteristics of the research data. In this study, the criteria used were in the form of prokem language words. The results of the study found seven prokem language words, namely "healing", "otw", "gibah", "pap", "japri", "goks", and "tuman". The use of prokem language by youth group youth groups is very diverse with regard to acronyms and abbreviations. Keywords: Prokem Language, Whatsapp, Youth Organization.